Wildlife and Indigenous Communities in Kenya: The influence of conservation education in supporting co-existence between wildlife and a Maasai community - Georgina Hoare; Kennedy Lemayian; Peter Higgins (Environmental Association of Southern Africa, 2022)
Human-wildlife conflict in Kenya is a complex issue with environmental, social, and economic dimensions. Conservation education can raise awareness of environmental issues, by increasing knowledge, promoting positive attitudes, leading to proenvironmental behaviours. Educated youth can become 'conservation ambassadors' who help spread messages through the community. This qualitative study critically examined the extent to which this took place using the Wildlife Warriors Kids education programme, in areas of human-wildlife conflict in Kenya. Data were collected on students' knowledge, attitudes and practice in three primary schools in Maasai areas; in one of these school areas, interviews and a focus group were also held with Maasai community members. The influence on students was evident, regarding knowledge about wildlife, positive attitudes and an understanding of pro-environmental behaviours. The filtration of knowledge and pro-environmental behaviours to the community level was positive but limited. Culture and human wildlife conflict were the predominant factors influencing attitudes. It was evident there is a need to include intergenerational learning, and focus attention on cultural and environmental challenges, to enhance the filtration of conservation education to the community.